Dampak Kepemimpinan dan Rotasi Kerja terhadap Turnover Intention - Mochammad Irfan; Arif Rachman Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
One of the major costs incurred by the company is the cost to maintain its human resources. These costs consist of recruitment costs and employee training costs. To reduce these costs, companies need to reduce turnover intention in their companies. The purpose of this study was to determine the impact of leadership and job rotation on employee turnover intention. This survey used multiple linear regression and SPSS 26 analyzed data from 79 respondents whose sample was determined using the census method. The results of this study found that turnover intention is partially significantly influenced by leadership. This result is followed by another variable, namely job rotation which partially also has a role in turnover intention. The two variables studied simultaneously play a significant and significant role on turnover intention